2022
DOI: 10.3390/foods11182885
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Antioxidant Effects of Kappa-Carrageenan Coatings Enriched with Cinnamon Essential Oil in Pork Meat

Abstract: Fresh pork is susceptible to microbial contamination and lipid oxidation, which leads to food safety and quality issues. This study aimed to develop a kappa-carrageenan (KC) coating embedded with cinnamon essential oil (CEO) for antimicrobial and antioxidant purposes in pork meat. The uncoated controls and coated samples were subjected to microbial (total viable count, lactic acid bacteria, and H2S-producing bacteria), chemical (DPPH and pH), and physical (surface color) analyses during refrigerated storage at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The thyme essential oil was used as an antiparasitic or to treat minor wounds from ancient times due to its strong antimicrobial properties [21,22]. Lavender [23,24], grapefruit [25,26], bergamot [27,28], cinnamon [29,30], and rosemary [31,32] essential oils have strong antimicrobial activity and therefore are good candidates for innovative antibacterial and antifungal therapies and materials. Nevertheless, the essential oils must be loaded or encapsulated in a matrix, be it organic or inorganic, to ensure a longer release profile, and a sustained antimicrobial activity [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…The thyme essential oil was used as an antiparasitic or to treat minor wounds from ancient times due to its strong antimicrobial properties [21,22]. Lavender [23,24], grapefruit [25,26], bergamot [27,28], cinnamon [29,30], and rosemary [31,32] essential oils have strong antimicrobial activity and therefore are good candidates for innovative antibacterial and antifungal therapies and materials. Nevertheless, the essential oils must be loaded or encapsulated in a matrix, be it organic or inorganic, to ensure a longer release profile, and a sustained antimicrobial activity [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with our findings, Li et al [52] analyzed the major components of EOs isolated from C. cassia bark to be (E)-cinnamaldehyde (69.75%), and 2-methoxycinnamaldehyde (5.92%). Also, Chahbi et al [38] identified (E)-cinnamaldehyde (69.15%) as the main compound of CCEO used in their study. Similarly, we have found out that the major component in the conception of CVBEO was (E)-cinnamaldehyde (44.1%).…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, CEO has been previously reported as a food preservative to inhibit fungal growth [34]. Indeed, to enhance the storage stability of food products, it has been applied in various fruits, such as apples [35], oranges [36], pomegranate [37], various types of meat [38,39], and dairy products [40,41]. Prior to our experiment, there are some papers revealing the effectivity of CEO application for bread preservation [42,43]; however, it is necessary to note that the antimicrobial activity of the same type of EO is multifactorial-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…The reported results showed a decline in the total plate counts, yeast and mold counts, total coliform counts, the lactic acid bacteria count and Listeria monocytogenes in the edible coatings containing 0.2% cinnamon oil [ 52 ]. In another study, He et al [ 60 ] determined the antimicrobial activity of kappa-carrageenan coatings enriched with cinnamon essential oil in pork meat in their work, and they reported that the coatings were able to delay the spoilage of pork meat for at least 2 days in comparison to that of the control. The effect of the xanthan coating containing various concentrations (0, 1, 2%; w / v ) of the ethanolic extract of propolis was studied regarding the microbial indices in mackerel fillets stored at 2 °C for 20 days by Sheikha et al [ 61 ].…”
Section: Resultsmentioning
confidence: 99%